2023
DOI: 10.1101/2023.03.05.531194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription factor interactions explain the context-dependent activity of CRX binding sites

Abstract: The effects of transcription factor binding sites (TFBSs) on the activity of acis-regulatory element (CRE) depend on the local sequence context. In rod photoreceptors, binding sites for the transcription factor (TF) Cone-rod homeobox (CRX) occur in both enhancers and silencers, but the sequence context that determines whether CRX binding sites contribute to activation or repression of transcription is not understood. To investigate the context-dependent activity of CRX sites, we fit neural network-based models… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 72 publications
2
9
0
Order By: Relevance
“…The contribution of the CRX motifs was calculated by comparing the difference in predicted activities of the background sequences versus the motif-containing sequences. The model predicted the known repressive effects of multiple CRX sites previously observed in both genomic and synthetic CREs (16,87).…”
Section: The Model Learned Relative Affinities and Known Contextual F...mentioning
confidence: 89%
“…The contribution of the CRX motifs was calculated by comparing the difference in predicted activities of the background sequences versus the motif-containing sequences. The model predicted the known repressive effects of multiple CRX sites previously observed in both genomic and synthetic CREs (16,87).…”
Section: The Model Learned Relative Affinities and Known Contextual F...mentioning
confidence: 89%
“…Results of prior MPRA studies show that whether CRX acts as an activator or repressor at a particular CRE depends on local motif composition (White et al 2013; White et al 2016; Hughes et al 2018; Friedman et al 2021; Loell et al 2023). We previously reported that CRX-bound silencers tend to have more copies of the CRX motif than enhancers do (White et al 2016; Friedman et al 2021), while enhancers contain more motifs for other photoreceptor TFs (Friedman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This model, trained on MPRA data from synthetic CREs with different combinations of photoreceptor TF binding sites, indicated that homotypic interactions between multiple copies of the CRX binding site were necessary to create repressive CREs. While the biophysical nature of these homotypic interactions is unknown, there is clear evidence that the presence of multiple copies of the CRX motif often leads to repression in both genomic and synthetic CREs (White et al 2016; Friedman et al 2021; Loell et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this is that different regulatory proteins can compete in their binding to shared motifs 13,14 . Another reason is that gene expression can be silenced when regulatory DNA contains multiple motifs for the same TF 15,1618 . For example, in mice, retinal “silencers” contains clusters of motifs for the TF CRX, while retinal “enhancers” contain a mixture of CRX and other TF motifs 16 .…”
Section: Introductionmentioning
confidence: 99%